Tackling Plant Meiosis: From Model Research to Crop Improvement - Lambing, Christophe; Heckmann, Stefan (Frontiers in Plant Science, 2018)
Genetic engineering and traditional plant breeding, which harnesses the natural genetic variation that arises during meiosis, will have key roles to improve crop varieties and thus deliver Food Security in the future. Meiosis, a specialized cell division producing haploid gametes to maintain somatic diploidy following their fusion, assures genetic variation by regulated genetic exchange through homologous recombination. However, meiotic recombination events are restricted in their total number and their distribution along chromosomes limiting allelic variations in breeding programs. Thus, modifying the number and distribution of meiotic recombination events has great potential to improve and accelerate plant breeding. In recent years much progress has been made in understanding meiotic progression and recombination in plants. Many genes and factors involved in these processes have been identified primarily in Arabidopsis thaliana but also more recently in crops such as Brassica, rice, barley, maize or wheat. These advances put researchers in the position to translate acquired knowledge to various crops likely improving and accelerating breeding programs. However, although fundamental aspects of meiotic progression and recombination are conserved between species, differences in genome size and organization (due to repetitive DNA content and ploidy level) exist, particularly among plants, that likely account for differences in meiotic progression and recombination patterns found between species. Thus, tools and approaches are needed to better understand differences and similarities in meiotic progression and recombination among plants, to study fundamental aspects of meiosis in a variety of plants including crops and non-model species, and to transfer knowledge into crop species. In this article, we provide an overview of tools and approaches available to study plant meiosis, highlight new techniques, give examples of areas of future research and review distinct aspects of meiosis in non-model species.